Adaptation of the Behavioural Regulation in Active Commuting to School (BR-ACS) Questionnaire in Portuguese Youth - Adilson Marques; Thiago Santos; Yolanda Demetriou; Dorothea M. I. Schönbach; Miguel Peralta; Pål Lagestad; João Martins; Dorota Kleszczewska; Anna Dzielska; Élvio R. Gouveia (MDPI AG, 2022)
This study aimed to translate and adapt the psychometric properties of the Behavioural Regulation in Active Commuting to School (BR-ACS) questionnaire to young Portuguese students. This study had two stages: (1) translation and adaptation of the questionnaire; (2) evaluation of the psychometric properties. A sample of 338 participants (212 female, 126 male) aged 11 to 19 years (Mage = 15.6 ± 2.1) from 31 cities and Madeira island participated in this study. The confirmatory factor analysis suggested an acceptable fit to the data for the first-order and third-order measurement models. The composite reliability values ranged from 0.71 (identified regulation) to 0.90 (integrated regulation), demonstrating internal consistency. The AVE values ranged from 0.40 (amotivation) to 0.69 (integrated regulation), demonstrating an acceptable convergent validity for all constructs. The model estimation had an acceptable fit, with values akin to those of the first-order tested model. Finally, the results of the multigroup analysis for the successive restricted models (CFI < 0.010 and RMSEA < 0.015) point out that the null hypothesis of factor invariance between gender cannot be rejected. The psychometric properties demonstrates the suitability of this questionnaire among Portuguese youths aged 11 to 19. This questionnaire will help understand the motivation aspects that underpin active commuting to school and consequently help to increase physical activity among Portuguese adolescents.